1989
DOI: 10.1159/000293515
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Localization of Vasoactive Intestinal Polypeptide and Its Influence on Contractile Activity in the Non-Pregnant and Pregnant Human Cervix

Abstract: The distribution of vasoactive intestinal peptide (VIP) was studied by immunofluorescence in cervical tissue of non-pregnant and pregnant women. VIP was localized in connection with blood vessels as well as among collagen fibres and smooth muscle cells. No difference was observed between non-pregnant and term pregnant women. The effect of VIP on cervical contractility was tested on isolated strips by superfusion in a tissue chamber. VIP inhibited contractions at 10––8––10––6M concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It has been proven that noradrenaline, which activates αand/or β-adrenergic receptors and enhances PGs production, inhibits the contractility of the uterus, either in its physiological or pathological state [46][47][48][49]. Similarly, VIP and NPY also play a role in contractility regulation [50,51]. Moreover, VIP, best recognized due to its antiinflammatory functions, is also known for its neuroprotective capabilities, which include enhancing neuronal survivability in cells under pathological conditions, such as inflammations [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that noradrenaline, which activates αand/or β-adrenergic receptors and enhances PGs production, inhibits the contractility of the uterus, either in its physiological or pathological state [46][47][48][49]. Similarly, VIP and NPY also play a role in contractility regulation [50,51]. Moreover, VIP, best recognized due to its antiinflammatory functions, is also known for its neuroprotective capabilities, which include enhancing neuronal survivability in cells under pathological conditions, such as inflammations [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that NA exerts an effect on the contractility in healthy [18,19] and inflamed [11] porcine uterus. Similarly, under physiological conditions, NPY, GAL and VIP regulate this uterine activity [22,25,26]. Thus, it is possible that the above-mentioned neurotransmitters may be involved in the elimination of the exudate from the uterus with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NPY, via its receptor subtype 1, stimulates the contractility of myometrium [22] and uterine arteries [23,24]. Similarly, GAL [25] and VIP [26] affect uterine contractility, while SOM regulates endometrial cell proliferation and motility [27].…”
Section: Introductionmentioning
confidence: 99%
“…An upregulation of populations expressing VIP and other neuronal factors confirms the properties of these substances. Best recognized for its anti-inflammatory functions, VIP plays a role in the regulation of contractility and enhances neuronal survivability in cells under pathological conditions, such as inflammations [53][54][55][56][57], whereas SOM changes motility and endometrial cell proliferation [58]. Moreover, it has recently been discovered that SOM influences contractile activity in inflamed uteri by increasing amplitude and decreasing frequency [59].…”
Section: Discussionmentioning
confidence: 99%